A highly efficient indirect ELISA and monoclonal antibody established against African swine fever virus pK205R - Li, Liwei; Qiao, Sina; Liu, Jiachen; Zhou, Yanjun; Tong, Wu; Dong, Shishan; Liu, Changlong; Jiang, Yifeng; Guo, Ziqiang; Zheng, Haihong; Zhao, Ran; Tong, Guangzhi; et al. (Frontiers in Immunology, 2023)
African swine fever (ASF) is a contagious infectious disease with high lethality which continuously threatens the global pig industry causing huge economic losses. Currently, there are no commercially available vaccines or antiviral drugs that can effectively control ASF. The pathogen of ASF, ASF virus (ASFV) is a double-stranded DNA virus with a genome ranging from 170 to 193 kb and 151 to 167 open reading frames in various strains, which encodes 150–200 proteins. An effective method of monitoring ASFV antibodies, and specific antibodies against ASFV to promote the development of prevention techniques are urgently needed. In the present study, pK205R of ASFV was successfully expressed in mammalian cells using a suspension culture system. An indirect enzyme-linked immunosorbent assay (ELISA) based on the purified pK205R was established and optimized. The monoclonal antibody (mAb) against pK205R recognized a conservative linear epitope (2VEPREQFFQDLLSAV16) and exhibited specific reactivity, which was conducive to the identification of the recombinant porcine reproductive and respiratory syndrome virus (PRRSV) expressing pK205R. The ELISA method efficiently detected clinical ASFV infection and revealed good application prospects in monitoring the antibody level in vivo for recombinant PRRSV live vector virus expressing the ASFV antigen protein. The determination of the conserved linear epitope of pK205R would contribute to further research on the structural biology and function of pK205R. The indirect ELISA method and mAb against ASFV pK205R revealed efficient detection and promising application prospects, making them ideal for epidemiological surveillance and vaccine research on ASF.